A chemometry of aldrovanda vesiculosa l. (waterwheel, droseraceae) populations - Płachno, Bartosz J.; Strzemski, Maciej; Dresler, Sławomir; Adamec, Lubomír; Wojas-Krawczyk, Kamila; Sowa, Ireneusz; Danielewicz, Anna; Miranda, Vitor F. O. [UNESP] (MDPI, 2021)
The genus Aldrovanda is a Palaeogene element containing a single extant species, Aldrovanda vesiculosa L. This aquatic carnivorous herb has a very wide range of distribution, natively covering four continents; however, it is a critically endangered aquatic plant species worldwide. Previous studies revealed that A. vesiculosa had an extremely low genetic variation. The main aim of the present paper is to explore, using chemometric tools, the diversity of 16 A. vesiculosa populations from various sites from four continents (Eurasia, Africa, Australia). Using chemometric data as markers for genetic diversity, we show the relationships of 16 A. vesiculosa populations from various sites, including four continents. Phytochemical markers allowed the identification of five well-supported (bootstrap > 90%) groups among the 16 populations sampled. The principal component analysis data support the idea that the strongly related African (Botswana) and Australian (Kimberley, NT, NW Australia) populations are the most distant ones, separated from the European and Asian ones. However, considering the five Australian populations sampled, three are nested within the Eurasian group. The chemometric data are correlated positively with the geographical distances between the samples, which suggests a tendency toward isolation for the most distant populations.
Keywords: Aquatic carnivorous plant; Carnivorous plant; Critically endangered aquatic species; Phenetics; Phylogeny; Plant taxonomy